Improvement of Clayey Soils by Combined Bamboo Strip and Flax Fiber Reinforcement - Fang Tong; Qiang Ma; Wenwen Xing (Advances in Civil Engineering)
A combined bamboo strips and flax fiber reinforcement method to reinforce clay is proposed in this paper, and in order to study the mechanical properties of bamboo strips and flax fiber-reinforced clay (BFRC), a series of tensile tests were carried out to obtain the relationship between the average tensile force and deformation of flax fiber and bamboo strip; after that, triaxial shear tests were carried out under the conditions of different confining pressures. In addition, the reinforcement mechanism of the bamboo strips and flax fiber-reinforced clay (BFRC) is analyzed. The test results show that the cohesion and internal friction angle of the bamboo strips and flax fiber-reinforced clay (BFRC) are improved compared with the pure clay. In the case of flax fiber-reinforced clay, the cohesion of reinforced clay is increased by 18.34% and the friction angle is only increased by 0.39%. In the case of bamboo strips and flax fiber-reinforced clay, the cohesion of reinforced clay is increased by 26.36% and the friction angle is only increased by 10.24%. The addition of bamboo strips improves the shear strength of the reinforced clay and effectively improves the deformation resistance of the flax fiber-reinforced clay (FRC). And it increases the internal friction angle and cohesion of the clay, although the increase in the strength is mainly reflected in the influence on the cohesion.